Saturation stress based models and their applicability to tensile flow behaviour of superalloy 617M. (August 2021) - Christopher, J.; Nandagopal, M.; Palaparti, D.P. Rao; Reddy, G.V. Prasad; Albert, Shaju K.
Abstract: Four different saturation stress based models were employed to investigate the uniaxial tensile deformation behaviour of boron added Alloy 617M. Voce relationship described the tensile flow behaviour of the alloy to a reasonable extent at high strain levels over the temperatures range of 300 K–1023 K. On the contrary, the employed macroscopic Estrin-Mecking model could not provide an adequate description to flow stress versus true plastic strain data at different temperatures. In addition to Estrin-Mecking and Voce relationships, two different saturation models (Model-I and Model-II) were empirically developed and used in the present investigation. The developed relationships provide a better description of Alloy 617M work hardening behaviour compared to the existing models. Relative applicability of the different relationships has been verified based on their predictive capability of the tensile properties such as true yield and ultimate tensile strength and true uniform plastic strain. It was found that the predicted tensile properties using Model-II are comparable with the experimental data than those prediction obtained from the other models. The predicted shear modulus compensated saturation stress exhibited a peak value at 923 K due to the occurrence of dynamic strain ageing as well as precipitation strengthening. In the temperatures ranging from 473 K to 973 K, the observed lower values in the temperature dependent rate constant associated with the Model-II suggested the reduced activity of dynamic recovery at intermediate temperatures compared to 300 K and 1023 K. The rapid decrease in saturation stress, true ultimate strength and uniform plastic strain is the clear indication of the dominance of dynamic recovery effects at 1023 K for the Alloy 617M. Highlights: New models were introduced to examine the flow behaviour of Alloy 617 M. Model-II appropriately predicted flow behaviour and tensile properties of the alloy. From 473 K to 973 K, the rate constant related to recovery displayed the lower value. Occurrence of DSA and precipitate hardening enhanced the saturation stress at 923 K. Rapid decrease in saturation stress indicated the dominance of recovery at 1023 K.